Sodium ion battery positive electrode sodium pre-modification method and sodium ion battery thereof
By adopting a multi-layer structure design in the positive electrode of the sodium ion battery, the pre-sodium functional layer is located on the surface of the current collector, combining sodium-rich materials and conductive agents, the reversible capacity and life of the sodium ion battery are solved, and the energy density of the battery is improved and cycle stability.
Patent Information
- Application Number
- CN202411492912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
AI Technical Summary
Existing sodium ion batteries have problems such as fast reversible capacity drop, low energy density and fast life attenuation, especially because the sodium supplementation agent is difficult to function effectively at the unfavorable position of the pole depth position, which affects the cycle life of the battery.
The positive electrode sheet design adopts a multi-layer structure, in which the pre-sodium functional layer is separated from the basic functional layer, the pre-sodium functional layer is located far away from the current collector surface, and the thickness ratio of the pre-sodium functional layer is controlled by tight multi-layer coating. At 1/10-1/20, sodium-rich materials such as Na2S, NaCrO2, Na2NiO2, etc., combined with layered metal oxides and polyanionic compounds, conductive agents and binders, and prepared by extrusion or ultrasonic spraying technology.
Improve the release efficiency of sodium ions, enhance the first charge and discharge efficiency and reversible capacity of the battery, ensure the structural stability and conductivity of the positive electrode sheet, extend the cycle life of the battery, and avoid the decomposition of the counter electrode sheet structure by sodium supplementation agent. The impact of
Smart Images

Figure CN119314998A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for pre-sodiumization of a positive electrode of a sodium ion battery and a sodium ion battery thereof. Background Art
[0002] The research and development and application of new energy storage battery technologies are playing an increasingly important role. At present, energy storage batteries are mainly developed in the direction of lithium-ion batteries. However, with the increasing scale of lithium-ion batteries, the uneven distribution and scarcity of lithium resources have gradually been exposed. The sharp fluctuations in the price of lithium carbonate have had a huge impact on the energy storage battery industry, so it is necessary to further find alternatives. Compared with lithium, sodium has a high content in the earth's crust and is widely distributed. The development of sodium-ion batteries can also effectively reduce costs. In addition, sodium-ion batteries have advantages in low-temperature performance, safety, and fast charging, which are more conducive to the promotion and application of sodium-ion batteries in the field of energy storage.
[0003] With the continuous development of sodium-ion battery technology, the related industrial chain has gradually emerged. Significant progress has been made in the research and development and production of key materials including positive electrode materials, negative electrode materials, and electrolytes. However, compared with lithium-ion batteries, the technical maturity of sodium-ion batteries still has certain problems, and the energy density and cycle life of the batteries need to be further improved. One of the key points is the first efficiency of the battery. Due to the difference between sodium ions and lithium ions, sodium-ion batteries need to use hard carbon and soft carbon as negative electrodes. The first charge and discharge process consumes a lot of active sodium ions, which causes the reversible capacity of the battery to decrease and the energy density of the battery to decrease.
[0004] The positive and negative electrode pre-sodiumization technology can reduce the consumption of active sodium and improve the reversible capacity. The positive electrode pre-sodiumization technology is considered to be a method that can achieve mass production in the pre-sodiumization method by adding sodium-rich compound materials and decomposing and releasing sodium ions under high pressure. Among the sodium-ion battery sodium replenishment methods currently in patents, most of the methods of directly mixing the sodium-ion battery pre-sodiumization materials with the positive electrode slurry to obtain the positive electrode sheet form a single-layer single-component positive electrode sheet. In this way, the sodium replenisher is used as a sodium ion sacrificial agent in the active material of the electrode sheet. During the first charging process, the sodium replenisher releases sodium ions and decomposes itself to produce gas overflow, and at the same time, structural vacancies are generated at the location, which affects the cycle life of the battery. At the same time, due to the influence of diffusion, the sodium replenisher located at a high depth of the electrode sheet is difficult to effectively play its role, thereby affecting the effectiveness of sodium replenishment. For example, CN202210893935.1 discloses a pre-sodiumization material for sodium-ion batteries, which is a method for obtaining a positive electrode plate by directly mixing it with a positive electrode slurry. During the first charge and discharge process of the plate prepared in this way, the pre-sodiumization material will decompose and release sodium ions, which will easily cause the internal structure of the positive electrode plate to collapse, causing the plate life to decay rapidly.
[0005] There are also reports that positive electrode plates are formed by constructing a pre-sodiumization layer. For example, CN117673252A discloses a sodium supplement layer and an active material layer that are sequentially arranged from the inside to the outside on at least one side of the current collector. The sodium supplement layer is formed by evenly mixing a sodium supplement agent and a dispersant to form a sodium supplement agent dispersion, and the sodium supplement agent dispersion is coated on the current collector. The formation of a layer of sodium supplement agent on the surface of the current collector will lead to problems with the electronic conduction of the electrode plate due to the poor conductivity of the sodium supplement agent. The internal sodium supplement agent layer will affect the bonding strength between the electrode functional layer and the current collector, especially after the sodium supplement agent is decomposed. Therefore, there is a need for a method of comprehensively applying the sodium supplement agent in the positive electrode plate, which can not only meet the requirements of sodium ion batteries for sodium supplement agents to improve the reversible capacity and energy density, but also take into account the structural stability of the electrode itself and the battery cycle life, and can meet the production needs of the electrode plate. The positive electrode plate sodium supplement method. Summary of the invention
[0006] The object of the present invention is to provide a method for pre-sodiumization of a positive electrode of a sodium ion battery and a sodium ion battery thereof, so as to solve the following technical problems: Existing sodium-ion batteries have problems such as rapid reversible capacity decline, low energy density, and rapid life decay.
[0007] The purpose of the present invention can be achieved through the following technical solutions: The present invention provides a method for pre-sodiumization of a positive electrode of a sodium ion battery, characterized in that it comprises the following steps: Mixing the pre-sodium material with the positive electrode slurry to form a pre-sodium functional slurry; Applying the positive electrode slurry on the current collector to form a basic functional layer; Applying the pre-sodium functional slurry on the base functional layer to form a pre-sodium functional layer; Wherein, the pre-sodium material is a sodium-rich material, and the sodium-rich material includes at least one of Na2S, NaCrO2, Na2NiO2, Na2CO2 or Na2C4O2.
[0008] In one embodiment of the present invention, the thickness ratio of the pre-sodium functional layer to the basic functional layer is 1:10-1:20.
[0009] In one embodiment of the present invention, the coating method of the pre-sodium functional slurry is extrusion coating or ultrasonic spraying.
[0010] In one embodiment of the present invention, the positive electrode slurry includes a positive electrode active material, and the positive electrode active material is selected from at least one of a layered metal oxide or a polyanion compound.
[0011] In one embodiment of the present invention, the layered metal oxide has a chemical formula of Na x M y Oz , where 0 < x ≤ l, 0 < y ≤ 1, l < z ≤ 2, and M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, or Sn.
[0012] In an embodiment of the present invention, the layered metal oxide includes NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaCu m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1), or at least one of them.
[0013] In an embodiment of the present invention, the chemical formula of the polyanion compound is Na x M y [(X m O) n- z , where M is selected from at least one of V, Mn, Fe, Co, or Ni, and X is selected from one of P, S, Si, or F.
[0014] In an embodiment of the present invention, the polyanion is at least one of Na3V2(PO4)3, Na3V2(PO4)2F3, NaFePO4, Na2Fe2(SO4)3, or Na2Fe2P2O7.
[0015] In an embodiment of the present invention, the positive electrode slurry further includes a conductive agent, a binder, and a solvent, where the conductive agent is at least one of conductive carbon black, acetylene black, graphene, or carbon nanotubes, the binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose, sodium alginate, or polyacrylic acid, and the solvent is at least one of N-methylpyrrolidone, dimethylformamide, or ethylene glycol dimethyl ether.
[0016] The present invention also provides a sodium-ion battery, which is characterized in that it includes a pre-sodiated positive electrode sheet prepared by the sodium-ion battery positive electrode pre-sodiating method described in any one of the above, and at least further includes a separator, a negative electrode sheet, and an electrolyte.
[0017] Advantages of the present invention: The present invention proposes a method for pre-sodiumization of a positive electrode of a sodium ion battery and a sodium ion battery thereof, wherein a positive electrode sheet with a multi-layer structure is prepared, a pre-sodiumization functional layer and a basic functional layer are designed separately, and a thickness ratio of the pre-sodiumization functional layer is achieved by controlling a tight multi-layer coating basis to be 1 / 10-1 / 20 of the thickness ratio of the functional layer. In the battery charge and discharge reaction, the positive electrode of this multi-layer structure has a higher wettability because the pre-sodiumization functional layer is on the side surface away from the current collector and directly contacts the electrolyte. During the first charge and discharge process of the battery, the pre-sodiumization functional layer plays a role first, which is beneficial to more efficient release of sodium ions from the sodium-rich material, and is completely released during the first charge process to supplement the SEI of the battery. The lithium consumed in the formation of the interface increases the content of active lithium, which is more effective for improving the first effect and reversible capacity of the battery. Therefore, compared with the sodium-rich material, after releasing sodium ions and decomposing, only the pre-sodium functional layer structure with a relatively small thickness will change, and the basic functional layer still maintains the original layer structure, which does not affect the compaction state and pore structure of the pole piece. Therefore, it makes up for the sodium supplement layer in the multilayer structure design in the current patent, which is designed in the middle or close to the collector side to bring about the sodium supplement agent efficiency and longitudinal pole piece structure problems, thereby ensuring the basic structural stability and conductivity of the positive pole piece, and ensuring the cycle life of the sodium ion battery while improving the reversible capacity. The positive pole piece prepared by the sodium ion battery positive electrode pre-sodiumization method provided by the present invention can not only realize the sodium supplement function of the positive pole piece, improve the first effect and reversible capacity of the battery, but also avoid the influence of the sodium supplement agent on the structure and performance of the positive pole piece after the decomposition in the battery, and improve the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0019] Figure 1 Schematic diagram of the structure of the positive electrode plate obtained in one embodiment of the present invention.
[0020] Figure 2 This is a scanning electron microscope image of the positive electrode sheet obtained in Example 1 of the present invention.
[0021] Figure 3 It is a charge and discharge curve diagram of the positive electrode sheet obtained in Example 2 of the present invention and Comparative Example 1.
[0022] Figure 4 It is a comparison chart of test data of the charge and discharge capacity, first efficiency and reversible capacity of the sodium ion battery obtained in Example 2 of the present invention and Comparative Example 1.
[0023] Figure 5 This is the cycle life graph of the sodium-ion batteries obtained in Example 3 of the present invention and Comparative Example 2.
[0024] Figure 6 This is the rate performance graph of the sodium-ion batteries obtained in Example 3 of the present invention and Comparative Example 2.
[0025] Marking description: 00, positive current collector; 11(21), basic functional layer; 12(22), pre-sodiation functional layer. Detailed implementation manners
[0026] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the protection scope of the present invention.
[0027] The present invention provides a method for pre-sodiation of a positive electrode of a sodium-ion battery to prepare a positive electrode sheet and obtain a sodium-ion battery with pre-sodiation of the positive electrode. The positive electrode sheet prepared by the method for pre-sodiation of the positive electrode of the sodium-ion battery is obtained, for example, through steps S10-S30.
[0028] Step S10: Mix the pre-sodiation material with the positive electrode slurry to form a pre-sodiation functional slurry.
[0029] Step S20: Coat the same positive electrode slurry as in step S10 on the positive current collector to form a basic functional layer.
[0030] Step S30: Coat the pre-sodiation functional slurry obtained in step S10 on the basic functional layer formed in step S20 to form a pre-sodiation functional layer.
[0031] Please refer to Figure 1 As shown, in an embodiment of the present invention, in step S10, the positive electrode slurry includes, for example, a positive electrode active material, a conductive agent, a binder, and a solvent. In this embodiment, the positive electrode active material is, for example, at least one selected from layered metal oxides or polyanion compounds. Among them, the chemical formula of the layered metal oxide is, for example, Na x M y O z , and 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, or Sn. In a specific embodiment of the present invention, for example, it further includes NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaCum Fe n Mn p O2 (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1). In this embodiment, the chemical formula of the polyanion compound is, for example, Na x M y [(X m O) n- ] z , and M is selected from at least one of V, Mn, Fe, Co or Ni, and X is selected from one of P, S, Si or F. In a specific embodiment of the present invention, it is at least one of Na3V2(PO4)3, Na3V2(PO4)2F3, NaFePO4, Na2Fe2(SO4)3 or Na2Fe2P2O7. In this embodiment, the conductive agent is at least one of acetylene black, graphene or carbon nanotubes, the binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose, sodium alginate or polyacrylic acid, and the solvent is at least one of N-methylpyrrolidone, dimethylformamide or ethylene glycol dimethyl ether. In this embodiment, the pre-sodium functional slurry includes, for example, a pre-sodium material and a positive electrode slurry, wherein the pre-sodium material is, for example, a sodium-rich material. In a specific embodiment of the present invention, the sodium-rich material includes at least one of Na2S, NaCrO2, Na2NiO2, Na2CO2 or Na2C4O2. In this embodiment, the pre-sodium material accounts for 5-20% of the total mass of the pre-sodium functional slurry, and the mass ratio of the pre-sodium material to the positive electrode active material is, for example, 1:4-1:6.
[0032] See also Figure 1As shown, in one embodiment of the present invention, in step S20 and step S30, the positive electrode current collector 00 can be selected from aluminum foil, etc., and the thickness of the positive electrode current collector is, for example, 8μm-15μm. The positive electrode slurry is coated on at least one side of the positive electrode current collector 00, and after drying, a basic functional layer 11 (21) is formed. In this embodiment, the viscosity of the positive electrode slurry is, for example, 5000-8000 mpa / s, and the thickness of the basic functional layer 11 (21) is, for example, 100-200μm, and another example is 100-120μm. After the basic functional layer 11 (21) is formed, a pre-sodium functional slurry is coated on the basic functional layer 11 (21), and after drying, a pre-sodium functional layer 12 (22) is formed, that is, the pre-sodium functional layer 12 (22) is, for example, arranged on the side of the basic functional layer 11 (21) away from the positive electrode current collector 00. In this embodiment, the coating process of the pre-sodium functional slurry is, for example, extrusion coating or ultrasonic coating, and the viscosity of the pre-sodium functional slurry is controlled to, for example, 2000-4000 mpa / s to achieve ultrasonic spraying requirements, or the viscosity is controlled to, for example, 5000-8000 mpa / s to achieve extrusion coating requirements. In this embodiment, the thickness of the pre-sodium functional layer 12 (22) is, for example, 1 / 10-1 / 20 of the thickness of the basic functional layer 11 (21), and for example, 10-20 μm.
[0033] The present invention also provides a sodium ion battery, comprising at least a positive electrode plate, a separator, a negative electrode plate and an electrolyte. Wherein, the sodium ion battery is, for example, a soft-pack sodium ion battery, and the separator is, for example, arranged between the positive electrode plate and the negative electrode plate. In this embodiment, the positive electrode plate is, for example, obtained after steps S10-S30, and the separator is, for example, a polypropylene film, and the thickness of the separator is, for example, 10-25 μm, and for example, 20 μm. In this embodiment, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode slurry layer coated on the negative electrode current collector. In this embodiment, the negative electrode current collector is, for example, aluminum foil, and the negative electrode slurry layer includes, for example, a negative electrode active material, a negative electrode conductive agent and a negative electrode binder, wherein the negative electrode active material is, for example, hard carbon, and the negative electrode conductive agent is, for example, one or more of conductive carbon black, acetylene black, carbon nanotubes or graphene, and the negative electrode binder is, for example, one or more of styrene-butadiene rubber, an aqueous polyacrylic acid derivative adhesive or a polytetrafluoroethylene emulsion.
[0034] In one embodiment of the present invention, the positive electrode sheet and the negative electrode sheet obtained above are roll-pressed, and the rolling density is, for example, 2.2-2.5 g / cm 3, after rolling, for example, it is cut into standard pole pieces by die-cutting equipment. In a specific embodiment of the present invention, the size of the positive pole piece after cutting is, for example, 56×43 mm, and the size of the negative pole piece after cutting is, for example, 58×45 mm. The cut positive pole piece, separator and negative pole piece are sequentially stacked and assembled to obtain a soft-pack battery cell, and then the electrolyte is injected. After the final sealing, for example, it is placed for 12 hours before forming. In this embodiment, the forming temperature is set to 45°C, for example, and the charging current is increased from 0.02C, 0.05C, and 0.1C in steps. After the battery voltage reaches, for example, 3.5-4.5V, it is switched to constant voltage charging until the current is, for example, less than 0.05C, and the formation is terminated to obtain a sodium ion battery, and the capacity of the battery cell is, for example, set according to the actual situation, and the sodium ion battery obtained by the present invention is tested, for example, by the following method.
[0035] To test the first efficiency of the sodium ion battery, the sodium ion battery obtained above is subjected to a charge and discharge cycle test at, for example, 0.1 C in the range of, for example, 1.5-4V, wherein the first efficiency = first cycle discharge capacity / formation charge capacity.
[0036] Testing the cycle performance of the sodium ion battery: The sodium ion battery obtained above is subjected to a charge and discharge cycle test at, for example, 0.2 C, in the range of, for example, 1.5-4 V, for 100 cycles.
[0037] Testing the rate performance of the sodium ion battery: The sodium ion battery obtained above was subjected to charge and discharge cycle tests at currents of, for example, 0.2 C, 0.33 C, 0.5 C, 1.0 C, and 2.0 C, for example, in the range of 1.5-4 V, and 5 cycles were performed at each current.
[0038] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0039] Example 1 A method for pre-sodiumization of a positive electrode of a sodium ion battery comprises the following steps: The positive electrode active material Na2Fe2(SO4)3, the pre-sodium material Na2NiO2, the conductive carbon black and the polyvinylidene fluoride were weighed respectively in a mass ratio of 80:15:2:3, 75 g of the polyvinylidene fluoride was added into a stirring tank containing 1500 g of the solvent N-methylpyrrolidone, and the mixture was stirred for 3 h until the N-methylpyrrolidone was completely dissolved. After the mixture was dissolved, 50 g of the conductive carbon black was added, and the stirring and dispersion were continued for 1 h until the conductive carbon black was completely dispersed. Then, 2000 g of the positive electrode active material Na2Fe2(SO4)3 and 375 g of the pre-sodium material Na2NiO2 were added at the same time. After the addition, the mixture was stirred and dispersed for 1 h, and the viscosity of the slurry was tested. By adding N-methylpyrrolidone, the final viscosity of the slurry was controlled to be between 2000 and 4000 mpa / s, and a pre-sodium functional slurry was obtained. The positive electrode active material Na2Fe2(SO4)3, conductive carbon black and polyvinylidene fluoride were weighed according to a mass ratio of 95:2:3, 75 g of polyvinylidene fluoride was added to a stirring tank containing 1500 g of solvent N-methylpyrrolidone, and the mixture was stirred for 3 h until the N-methylpyrrolidone was completely dissolved. After the mixture was dissolved, 50 g of conductive carbon black was added, and the mixture was stirred and dispersed for 1 h until the conductive carbon black was completely dispersed. Then, 2000 g of positive electrode active material Na2Fe2(SO4)3 was added, and the mixture was stirred and dispersed for 1 h. Then, the viscosity of the slurry was tested. By adding NMP, the viscosity of the slurry was controlled to be 5000-8000 mpa / s to obtain a positive electrode slurry. The positive electrode current collector aluminum foil is installed on an automatic coating machine, the running speed of the coating machine is controlled to be 1 m / min, and the oven temperature is 105°C. The above-mentioned positive electrode slurry is coated on the surface of the aluminum foil and dried by controlling and adjusting the transfer coating to obtain a basic functional layer with a thickness of 100-120 μm. Then, the above-mentioned pre-sodium functional slurry is sprayed on the basic functional layer by ultrasonic spraying, dried, and the spraying thickness is controlled to be between 10-20 um by controlling the spraying time and the number of superpositions to obtain a positive electrode sheet with a pre-sodium functional layer formed on the basic functional layer.
[0040] The preparation of sodium ion battery includes at least the following steps: The negative electrode active material, the negative electrode conductive agent and the negative electrode binder are mixed to prepare a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector, and dried to obtain a negative electrode sheet; The positive electrode sheet and the negative electrode sheet obtained above were rolled and cut to control the compaction density to 2.2-2.5 g / cm 3 The rolled positive electrode sheet is cut into a standard positive electrode sheet of 56×43 mm by a die-cutting device, and the negative electrode sheet is cut into a standard positive electrode sheet of 56×43 mm; The above-mentioned standard positive electrode plate, polypropylene separator and standard negative electrode plate are assembled into a soft-pack sodium-ion battery, and the electrolyte is injected. After the final sealing, it is placed aside for 12 hours and then formed. The formation temperature is 45°C, and the charging current is increased in steps from 0.02 C, 0.05C, and 0.1C. After the battery voltage reaches 3.6 V, it is switched to constant voltage charging until the current is less than 0.05 C, and the formation is terminated to obtain a sodium-ion battery.
[0041] The obtained positive electrode sheet and sodium ion battery were subjected to electrical performance tests, and the voltage range used in the first efficiency, cycle, and rate performance tests was 1.5-3.4 V.
[0042] Example 2 Using layered oxide NaNi m Fe n Mn p O2 is the positive electrode active material, Na2C4O4 is used as the pre-sodium material, the voltage upper limit of the formation process is set to 4.2V, and the voltage range used in the first efficiency, cycle and rate performance tests is 1.5-3.95 V. The other components and steps are consistent with Example 1.
[0043] Example 3 Using layered oxide NaCu m Fe n Mn p O2 is the positive electrode active material, Na2CO3 is used as the pre-sodium material, and a double-layer coating die is used in the coating process to realize double-layer simultaneous extrusion coating. By controlling the gap of the double-layer die, the supply speeds of the two feeding devices containing the pre-sodium layer slurry and the basic functional layer slurry are controlled respectively, the proportion of the pre-sodium functional layer and the basic functional layer is adjusted, the coating thickness of the basic functional layer is controlled to be 250μm, and the coating thickness of the pre-sodium functional layer is controlled to be 25-50μm. The other components and steps are consistent with Example 2.
[0044] Comparative Example 1 Without preparing pre-sodium functional slurry, a single positive electrode slurry is directly extruded and coated on the positive electrode current collector to form a single basic functional layer. The other components and steps are consistent with Example 2, and the basic functional layer obtained after drying has the same thickness and surface density as the basic functional layer and pre-sodium layer obtained in Example 2.
[0045] Comparative Example 2 Without preparing positive electrode slurry, a single pre-sodium functional slurry is extrusion coated on the surface of aluminum foil to form a single pre-sodium functional layer. The other components and steps are consistent with Example 3, and the pre-sodium functional layer obtained after drying has the same thickness and surface density as the basic functional layer and pre-sodium layer obtained in Example 3.
[0046] Observe the scanning electron microscope image of the positive electrode sheet obtained in Example 1.
[0047] The performance of the obtained positive electrode sheet and sodium-ion battery was tested.
[0048] See also Figure 2 As shown, Figure 2 This is a scanning electron microscope image of the cross-section of the positive electrode plate prepared by the positive electrode pre-sodiumization method obtained in Example 1 of the present invention. The image shows that the pre-sodiumization functional layer is located on the surface of the basic functional layer, and the thickness accounts for a relatively small proportion, indicating that even if the pre-sodiumization functional layer releases sodium ions and decomposes, the basic functional layer still maintains the original intra-layer structure, and has no effect on the compaction state and pore structure of the plate, thereby avoiding the performance of the sodium ion battery being affected by changes in the plate.
[0049] See also Figure 3 and Figure 4 As shown, Figure 3 The charge and discharge curves of the positive electrode sheets obtained in Example 2 and Comparative Example 1 are shown in FIG. Figure 4 The figure is a comparison chart of the test data of the charge and discharge capacity, first efficiency and reversible capacity of the sodium ion battery obtained in Example 2 and Comparative Example 1. By comparison, it can be seen that in the present invention, by constructing a pre-sodium functional layer on the surface of the basic functional layer, the capacity of the battery can be effectively improved, the first charge and discharge efficiency of the battery can be improved, and the gram capacity of the positive electrode material can also be significantly improved, which shows that the pre-sodium functional layer has an excellent pre-sodium effect.
[0050] See also Figure 5 and Figure 6 As shown, Figure 5 is a cycle life diagram of the sodium ion battery obtained in Example 3 and Comparative Example 2, Figure 6 It is a rate performance diagram of the sodium ion battery obtained in Example 3 and Comparative Example 2. By comparison, it can be seen that the capacity retention rate of the sodium ion battery in Example 3 is increased from 79.37% to 82.46%, the cycle stability is significantly improved, and its rate performance is better. At high rates, the capacity retention rate of the pole piece obtained in Example 3 is better, and the capacity retention rate of 2 C / 0.2C is increased from 56.48% to 74.28%, indicating that the multilayer structure of the pre-sodium functional layer and the basic functional layer adopted in the present invention has a better pre-sodium effect than the single layer obtained by directly mixing the pre-sodium material with the active material, and can improve the cycle stability and capacity retention rate of the sodium ion battery.
[0051] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0052] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for pre-sodiumization of a positive electrode of a sodium ion battery, characterized in that: The following steps are involved: Mixing the pre-sodium material with the positive electrode slurry to form a pre-sodium functional slurry; Applying the positive electrode slurry on the current collector and drying it to form a basic functional layer; The pre-sodium functional slurry is coated on the base functional layer and dried to form a pre-sodium functional layer; Wherein, the pre-sodium material is a sodium-rich material, and the sodium-rich material includes at least one of Na2S, NaCrO2, Na2NiO2, Na2CO2 or Na2C4O2.
2. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 1, wherein The thickness ratio of the pre-sodium functional layer to the basic functional layer is 1:10-1:
20.
3. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 1, wherein The pre-sodium functional slurry is coated by extrusion coating or ultrasonic spraying.
4. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 1, wherein The positive electrode slurry includes a positive electrode active material, and the positive electrode active material is selected from at least one of a layered metal oxide or a polyanion compound.
5. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 4, characterized in that: The chemical formula of the layered metal oxide is Na x M y O z , where 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, and M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, or Sn.
6. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 5, characterized in that: The layered metal oxide includes NaNi m Fe n Mn p O2(m+n+p=1,0≤m≤1,0≤n≤1,0≤p≤1) or NaCu m Fe n Mn p At least one of O2(m+n+p=1,0≤m≤1,0≤n≤1,0≤p≤1).
7. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 4, characterized in that: The chemical formula of the polyanion compound is Na x M y [(X m O) n- ] z , wherein M is selected from at least one of V, Mn, Fe, Co or Ni, and X is selected from one of P, S, Si or F.
8. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 7, characterized in that: The polyanion is at least one of Na3V2(PO4)3, Na3V2(PO4)2F3, NaFePO4, Na2Fe2(SO4)3 or Na2Fe2P2O7.
9. The method for pre-sodiumization of a positive electrode of a sodium ion battery according to claim 1, characterized in that: The positive electrode slurry also includes a conductive agent, a binder and a solvent, wherein the conductive agent is at least one of conductive carbon black, acetylene black, graphene or carbon nanotubes, the binder is at least one of polyvinylidene fluoride carboxymethyl cellulose, sodium alginate or polyacrylic acid, and the solvent is at least one of N-methylpyrrolidone, dimethylformamide or ethylene glycol dimethyl ether.
10. A sodium ion battery, characterized in that: The method comprises preparing a pre-sodiumized positive electrode sheet by the method for pre-sodiumization of a positive electrode of a sodium ion battery as described in any one of claims 1 to 9, and further comprises at least a diaphragm, a negative electrode sheet and an electrolyte.
Citation Information
Patent Citations
Pre-sodium-modified material, preparation method thereof, positive plate and sodium battery
CN115172734A
Sodium-ion battery positive electrode pre-sodium-modified pole piece and preparation method thereof
CN117673252A
Cited By
Preparation method of sodium sulfide carbon confinement pre-sodium coating based on monatomic catalysis
CN120978015A
Preparation method of sodium sulfide carbon limited pre-sodium coating based on single atom catalysis
CN120978015B
Positive / negative electrode coupled pre-sodium-modified sodium ion battery and construction method thereof
CN121618065A